Reninoma: a rare cause of curable hypertension - Ji Hye Kim; Ji Hyun Kim; Myung Hyun Cho; Eujin Park; Hye Sun Hyun; Yo Han Ahn; Hee Gyung Kang; Kyung Chul Moon; Il-Soo Ha; Hae Il Cheong (Korean Pediatric Society, 2019)
The most common type of refractory hypertension found in children is secondary hypertension, which is a potentially curable disease. Reninoma, a renin-secreting juxtaglomerular cell tumor, is a rare cause of severe hypertension that is usually diagnosed in adolescents and young adults. Surgical resection of the tumor completely cures the hypertension of patients with reninoma. The typical clinical presentation of reninoma includes hypokalemia, metabolic alkalosis, and features secondary to the increased activation of the renin-angiotensin system without renal artery stenosis. We report a case of reninoma in a female adolescent with a typical clinical presentation, in which surgical removal of the tumor completely cured hypertension. We discuss here the clinical features, imaging studies, and immunohistochemical examination of the tumor used to establish the diagnosis of reninoma and for the management of the condition.